Pengaruh Kinerja Perusahaan Terhadap Harga Saham Perusahaan Automotif and Component di Bursa Efek Indonesia - Leni Yuliyanti (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2014)
Share prices are much influenced by some factors among other things financial performance,rates of interest, rates of exchange, inflation rates and other factors, supplies and demands, volatility of share prices, trade volumes and so forth. One of barometers being used is financial performance. Such a financial performance might be seen from financial risk. Purpose of the research is to know influence of financial performance produced by PER, PBV and EPS on automotive and spare part company’s share prices in the Indonesia’s Stock Exchange. Population of the research is automotive and spare part company by using purposive sample. Hypothesis verification employs multiple correlation analysis by using SPPS 20 for windows. The results of the research demonstrated that financial performance has a significant influence upon share prices.